A new method for determining the 3D spatial orientation of molar microwear. Issue 6 (26th June 2015) - Tausch, Jeremy; Kullmer, Ottmar; Bromage, Timothy G.
Summary: Many types of behavioral and dietary information can be extracted from studies of tooth microwear. Some studies have even been successful at determining the overall directionality of microwear in order to establish gross masticatory movement (Williams et al., 2009, PNAS, 106, 11194–11199). However, microwear has never been successfully visualized in situ in 3 dimensions (3D), visualized virtually and quantified. The ability to accomplish this yields information on exact masticatory movement which can then be used to address any number of eco‐biological and physiological questions in extant and extinct organisms. In order to create 3D virtual reality (VR) representation of microwear, fossil molars from the Javanese Sangiran 7 (S7) Homo erectus tooth collection and from historic hunter/gatherer meta‐populations were imaged, the microwear in 3 dimensions was extracted, this information was then placed back on VR representations of the molars and quantified. The methodology contained herein demonstrates the efficacy and importance of such a technique in determining gross masticatory movement in fossil and recent hominin molars. This methodology could, in theory, be applied to any organism which produces microwear on its dentition. Applications in the fields of dentistry, orthodontics, climatology and dietary and habitat reconstructions can also be envisioned. SCANNING 37:446–457, 2015. © 2015 Wiley Periodicals, Inc.